ANALISIS PENGGUNAAN BAHASA INDONESIA TERHADAP KEJELASAN LAPORAN KEUANGAN MAHASISWA AKUNTANSI - Arya Dibangga Simatupang; Julfandi Julfandi; Rizki Amelia; Angela Ririn Angelin Bago; Zaki Muhammad Helmi; Muhammad Afiq Ghonim; Muhammad Hanif Kurniawan; Sulthan Alif Baihaqi; Lina Herlina; Perawati Perawati (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The correct use of Indonesian plays a crucial role in preparing financial reports, particularly for accounting students. Clarity of language not only influences reader comprehension but also determines the accuracy of the presentation of financial information. This article aims to analyze the use of Indonesian in the clarity of accounting students' financial reports, based on a review of several relevant journals. The method used is a literature review, reviewing previous research that addresses linguistic aspects of financial report writing. The analysis reveals several weaknesses in the use of Indonesian, such as inaccurate sentence structure, inconsistent terminology, and spelling and punctuation errors. These issues contribute to the decreased clarity and accuracy of financial reports. Therefore, it is necessary to improve accounting students' language skills so they can prepare clear, systematic financial reports that comply with Indonesian language rules.